Strategy for the elimination of Riba with special reference to existing debts - Tahir, Sayyid (Markazi Anjuman Khuddam-ul-Qur'an, Lahore (Pakistan), 1997)
This paper explicates the methodology followed by the Prophet SAAWS for elimination of riba during his lifetime, with reference to the Qur'an and the Hadith. It then draws inferences for a strategy that may be followed for elimination of riba with special reference to Pakistan. It also states specific measures as well as line of Pakistan for Islamizing the banking, including how to handle the issue of existing debts.